Efficacy of Probiotics Compared to Chlorhexidine Mouthwash in Improving Periodontal Status: A Systematic Review and Meta-Analysis - Kaio Henrique Soares; Parsa Firoozi; Glaciele Maria de Souza; Olga Beatriz Lopes Martins; Saulo Gabriel Moreira Falci; Cassio Roberto Rocha dos Santos (Hindawi Limited, 2023)
Purpose. To critically evaluate the available literature and conduct a systematic review of recent randomized controlled trials to assess the effectiveness of probiotics compared to chlorhexidine mouthwash in enhancing periodontal health. Methods. Five databases were searched electronically, as well as the gray literature. Using the Cochrane risk-of-bias tool for randomized clinical trials, the risk of bias was examined. The weighted mean difference (WMD) method was used to calculate the effect sizes. Heterogeneity was assessed using I2 and τ2 statistics. The GRADE approach was adopted to assess the certainty of the evidence. To assess the robustness of the findings, sensitivity analysis and publication bias assessment were undertaken. Results. A total of 1850 studies were initially identified. Sixteen clinical trials were eligible for qualitative synthesis, and ten were included in the meta-analysis. In terms of the gingival index, in total, no statistically significant difference was observed between chlorhexidine and probiotics within 4 weeks (WMD −0.03, 95% CI: −0.09∼0.04, P = 0.3885). Similar to GI, no statistically significant difference was observed between chlorhexidine and probiotics regarding the plaque index within 4 weeks (WMD 0.11, 95% CI: −0.05∼0.28, P = 0.1726). No statistically significant difference was observed between chlorhexidine and probiotics in all time intervals regarding oral hygiene index-simplified (WMD −0.01, 95% CI: −0.05∼0.04, P = 0.7508). The robustness of these findings was confirmed by sensitivity analysis and publication bias assessments. Conclusions. Based on the findings, probiotics were an acceptable alternative to conventional chlorhexidine in improving periodontal health. High-quality studies with rigorous methodology should be conducted to assess the optimum doses of probiotics for clinical implications.